Introduction to the Neuropsychological Norms for the US-Mexico Border Region in Spanish (NP-NUMBRS) Project. Issue 2 (17th February 2021) - Marquine, María J.; Rivera Mindt, Monica; Umlauf, Anya; Suárez, Paola; Kamalyan, Lily; Morlett Paredes, Alejandra; Yassai-Gonzalez, David; Scott, Travis M.; Heaton, Anne; Diaz-Santos, Mirella; Gooding, Amanda; Artiola i Fortuny, Lidia; et al.
Abstract: Objective: The present introduction to the Neuropsychological Norms for the U.S.-Mexico Border Region in Spanish (NP-NUMBRS) project aims to provide an overview of the conceptual framework and rationale that guided the development of this project. Methods: We describe important aspects of our conceptual framework, which was guided by some of the main purposes of neuropsychological testing, including the identification of underlying brain dysfunction, and the characterization of cognitive strengths and weakness relevant to everyday functioning. We also provide our rationale for focusing this norm development project on Spanish-speakers in the United States, and provide an outline of the articles included in this Special Issue focused on the NP-NUMBRS project. Conclusions: The data presented in this Special Issue represent an important tool for clinicians and researchers working in the neuropsychological assessment of Spanish-speakers in the United States.